Dealing with late maternal death due to cardiovascular disease - Sliwa, Karen (SA Heart Journal, 2017)
Globally, cardiac disease is emerging as an important indirect cause of maternal death. Cardiac conditions can be pre-existing, such as the case with rheumatic heart disease or congenital heart disease which can be unmasked by the increased haemodynamic load in pregnancy, or they can be caused by pregnancy, e.g. hypertensive disorders or peripartum cardiomyopathy (PPCM).